The book collection of the Sambian bishop John Clare from Toruń (1310-1344) - Biskup, Radosław; Czyżak, Marta (Folia Toruniensia, 2012)
The examination of the book collection donated by John Clare to the chapter library brings surprising results. The bishop gave to the chapter 17 volumes: 7 books concerning canon law and 7 works concerning theology. Among the canonistic works we can find the most important medieval collections of church law: The Decretum Gratiani and The decretals of Gregory IX, the commentary on the Decretals of Gregory IX by Heinrich von Merseburg, and the outline of church law concerning the election for church positions by William de Mandagoto. Among the theological works we can distinguish two most important medieval syntheses: Sentences by Peter Lombard and Secunda secundae – the most widely-read part of the Summa by Thomas Aquinas and his two volumes of the Catena, translated into German a few decades later on the initiative of the order. The mysterious “illuminated code” may be regarded as the first version of Speculum humanae salvationis, the anonymous work showing the history of salvation in miniatures, which was copied on the walls of the organ gallery in the cathedral in Königsberg. The codes donated to the chapter are the evidence that the benefactor was a man of great intellect, who cared for the legal and theological education of the cathedral clergy. They also reflect the processes of forming new church administration in the bishopric of Sambia, whose protagonist in the years 1294-1344 was John Clare from Toruń – a member of the cathedral chapter and bishop. The book collection might have inspired the development of art and writing in German in the Teutonic Order.